The Paradox of Power in CSR: A Case Study on Implementation - Bondy, Krista (Springer, 2008)
Purpose Although current literature assumes positive outcomes for stakeholders resulting from an increase in power associated with CSR, this research suggests that this increase can lead to conflict within organizations, resulting in almost complete inactivity on CSR. Methods A single in-depth case study, focusing on power as an embedded concept. Results Empirical evidence is used to demonstrate how some actors use CSR to improve their own positions within an organization. Resource dependence theory is used to highlight why this may be a more significant concern for CSR. Conclusions Increasing power for CSR has the potential to offer actors associated with it increased personal power, and thus can attract opportunistic actors with little interest in realizing the benefits of CSR for the company and its stakeholders. Thus power can be an impediment to furthering CSR strategy and activities at the individual and organizational level.
Keywords: Corporate social responsibility; Implementation; Power; Resource dependence theory; Case study; Empirical